Assessment of Barriers to the Implementation of Smart Contracts in Construction Projects-Evidence from Turkey - Budayan, Cenk; Okudan, Ozan (MDPI, 2023)
Despite their promising potential, the level of implementation of smart contracts is not at the desired level. To expedite the acceptance and deployment of smart contracts, the barriers to the implementation of smart contracts should be revealed. Past studies, however, do not provide a comprehensive theoretical basis due to several methodological drawbacks. Thus, this study aims to identify and assess the barriers to the implementation of smart contracts by considering the inherent characteristics of the construction industry. An in-depth literature review was initially conducted to extract all barriers proposed in the literature. Then, focus group discussion (FGD) sessions were conducted with the participation of the construction practitioners. In the FGD session, the results of the literature review were validated, and nine additional barriers were proposed. Finally, a total of 20 barriers under five categories was proposed for the smart contract adoption in the construction industry. Then, a questionnaire survey was conducted with the participation of 15 construction practitioners. Lastly, fuzzy VIKOR analysis was performed to assess the criticality of the implementation barriers. This study indicates that the construction companies should overcome not only technical barriers but also managerial barriers. Changes in the processes arisen due to smart contract implementation prevent the construction from implementing a smart contract, since the employees show resistance to these changes. Furthermore, the companies believe that they can lose their bargaining power with smart contracts, and they do not want to lose their power. Bottlenecks are considered the most critical barrier from a technological perspective, and companies are concerned about the problems resulting from them. Although this study provides insights into the barriers to smart contracts in the construction industry, all the respondents are from Turkey. Therefore, some of the findings of this study can be specific to the Turkish construction industry.
Keywords: civil engineering; construction management; construction projects; smart contracts; implementation barriers; contract management; fuzzy VIKOR; multi-criteria decision making (MCDM); FOCUS GROUP; BLOCKCHAIN; ENVIRONMENT; CHALLENGES; INDUSTRY; SCIENCE; SCOPUS; MODEL; WEB; Construction & Building Technology; Engineering